PENERAPAN AKAD BISNIS ONLINE DALAM PERSPEKTIF ISLAM - Helmy Syamsuri; Abdul Sumarlin; Rahman Ambo Masse (Jurnal Teknologi Pendidikan Madrasah, 2024)
This research aims to understand and increase insight into contracts in business and online transactions from an Islamic perspective, by studying and analyzing how contracts in online business and online transactions work, by identifying contracts in online business, formulating online business contract schemes, as well as product-based Online business contracts from an Islamic perspective are based on the provisions of the DSN-MUI fatwa. This research uses the library research method or literature review with data collection carried out in several stages starting from collecting references to analyzing references that are relevant to this research. The data sources needed in writing this research are secondary data, namely from document data and related research libraries. with research, including: Al-Qur'an, hadith, MUI Fatwa, related journals, and book literature. The results of the analysis in this research show that online business is permitted according to Islam as long as it does not contain elements that could damage it and fulfills the pillars and conditions in buying and selling. The online buying and selling mechanism has been regulated in DSN-MUI Fatwa No. 110/DSN-MUI/IX/2017 concerning buying and selling contracts, DSN MUI fatwa No. 144/DSN-MUI/XII/2021 concerning marketplaces based on sharia principles, DSN MUI fatwa No. 146 /DSNMUI/XII/2021 concerning online shops based on sharia principles